Prospek Kelembagaan Transmigrasi: Demokratisasi Administrasi Program Transmigrasi - Ratminto Ratminto (Jurnal Administrasi Publik, 2004)
Although there were controversies over the implementation of transmigration program, the program are still in need either for national or local interest. Social-environment context which always changes have demanded reinventions toward the program and the institutionalization of transmigration. The betterment of the program and institutonalization by applying regional approach and administrative democratization is become necessary. Therefore the support for nation building will be strengthened as well developing partnership mechanism in program management that will result in the attainment of the program goal.Kata Kunci : transmigrasi, mobilitas penduduk, kelembagaan, demokratisasi administrasi